Parameters controlling the electrokinetic deposition of multi-walled carbon nanotubes as biosensing thin films - Abdulhameed, Abdullah; Halin, Izhal Abdul; Mahnashi, Yaqub; Buyong, Muhamad Ramdzan (Springer, 2024)
Solid-state biosensors, particularly those based on nanomaterials, represent a remarkable advancement in sensor technology. The fabrication methods and nanomaterial processing techniques highly influence the performance of these biosensors. This work investigates the parameters controlling the deposition of multi-walled carbon nanotubes (MWCNTs) on glass substrates using dielectrophoresis (DEP) as a biosensing thin film. The parameters include the deposition configuration, medium properties, electrode shape, MWCNT concentration, and sonication time. A high DEP force of 3.85 × 10–8 N was observed when de-ionized water (DIW) was used as a medium while depositing MWCNTs from dimethylformamide (DMF) produced uniform thin film with less distortion. The shape of the electrode tip is critical in determining the thickness and width of the deposited thin film. Round-shaped tips were found to be more suitable for controllable deposition where the width of the deposited MWCNTs increases linearly 5 μm per minute. The parameters of the MWCNTs themselves are also studied. It was found that a sonication time of 40 min was enough to disperse MWCNTs without causing any structural damage to their walls. Further, a weight ratio of 0.0005 wt. % was enough to form complete bridges of MWCNT across the electrode gap. Controllable deposition of nanomaterials such as MWCNTs is highly desirable in the construction of biosensing layers in order to precisely control the performance and characteristics of the fabricated biosensors.